Optimizing the use of cranes and trucks in forestry operations (2017)
In this paper, a real-world forestry transport planning problem is presented. A mathematical programming model has been developed for the assignment of loading cranes and the transport of logs. For the solution, GAMS and CPLEX modeling systems were used. An MS Excel interface was used for both data and parameter loading and result analysis. This allows input data to be loaded and modified quickly and data to be analyzed in an approachable manner. In addition, decisions can be made expeditiously. The model was applied to a Chilean forestry company under multiple scenarios, and the results were obtained in a reasonable computational time (less than 1 minute), in relation to those required for decision-making.